Evaluasi UI/UX Website Informasi Desa Una Mendaa Menggunakan Prinsip Heuristik Nielsen - UMY RAMADHANI SENGA; Muhammad Rifqi Geroda Lawan; Waode Rina Harmawati; Nopal Agusan Rian; Muhammad Rizky; Zila Razilu (Universitas Muhammadiyah Tangerang, 2026)
Advances in digital technology have brought significant changes in information delivery at the village government level, with websites becoming a strategic medium for supporting transparency, public communication, and digital services to the community. This study aims to evaluate the quality of user interface (UI) design and user experience (UX) on the Una Mendaa Village Information Website using Nielsen's ten heuristic principles, including visibility, real-world relevance, user freedom, consistency, error prevention, recognition versus recall, efficiency, aesthetics, error recovery, and documentation. The research method included observations of eight main displays and news pages, and the distribution of questionnaires to 20 user respondents. Analysis was conducted using descriptive quantitative and qualitative methods to assess the level of usability of the system. The results showed a user satisfaction level of 85.2%, with the highest score for the consistency and standards principle (90%) and the lowest for error prevention (78%). In general, the website design was considered attractive, easy to understand, and relevant to the local context, but improvements in the navigation and form validation systems are still needed to optimize the user experience and support the goals of digital-based village government.Keywords: UI/UX, Nielsen Heuristics, Village Website, Interface Evaluation, User Experience.